The Role of Ion Channels in Pulmonary Hypertension: A Review - Han‐Fei Li; Xin‐Yao Li; Yu‐Qing Sun; Ze‐Ying Zhi; Liao‐Fan Song; Meng Li; Yi‐Ming Feng; Zhi‐Hao Zhang; Yan‐Feng Liu; Yu‐Jing Chen; Fan‐Rong Zhao; Tian‐Tian Zhu (Pulmonary Circulation)
ABSTRACT Pulmonary hypertension (PH) constitutes a critical challenge in cardiopulmonary medicine with a pathogenesis that is multifaceted and intricate. Ion channels, crucial determinants of cellular electrochemical gradient modulation, have emerged as significant participants in the pathophysiological progression of PH. These channels, abundant on the membranes of pulmonary artery smooth muscle cells (PASMCs) and pulmonary artery endothelial cells (PAECs), pivotally navigate the nuanced interplay of cell proliferation, migration, and endothelial function, each vital to the pulmonary vascular remodeling (PVR) hallmark of PH. Our review delves into the mechanistic insights of potassium, calcium, magnesium, zinc, and chloride ion channels in relation to their involvement in PH. It not only emphasizes the notable advances and discoveries that cast these ion channels as underlying factors in the etiology and exacerbation of PH but also highlights their potential as innovative therapeutic targets.